A soft-switched current-controlled converter for induction machine drives. - De Andrade, D.A (IEEE Transactions on power electronics)
The paper proposes a current controlled inverter operating in zero voltage switching (ZVS) mode for an induction machine drive. Operation with no voltage stress in the DC link bus is achieved. Together with the soft switching operation, a fixed frequency bang-bang current control technique is also implemented to allow for an accurate shaping of sinusoidal currents to feed the motor. As a result, a ripple free torque profile in steady state operation is achieved. With the soft switching technique it is possible to operate conventional IGBTs at 40 kHz. A detailed analysis of the circuit operation is presented. The feasibility of the proposed scheme is experimentally verified on a prototype